Managerial control: a study among public/private relations from the perspective of transaction cost theory - Júlio Ricardo Rezende da Costa; Karla Katiuscia Nóbrega de Almeida (Revista Ambiente Contábil)
Purpose: The present study investigated contractual characteristics and management control mechanisms in public contracts for assignment of use in a Military Organization (MO) of the Brazilian Army, and characterized the transactions object of the studied contracts and the form of governance adopted, according to the precepts of the Transaction Cost Theory (TCT).